Social Construction of Cultural Acculturation in the Friday Legi Mass in Pohsarang Village, Kediri Regency, Indonesia - Anggit Yuniar Putri Pilhandesi; Jhezkiel Enrico Laksmana (PT Pro Panoramic Solution, 2026)
This study examines the dynamic relationship between the Catholic Church and local culture within the context of liturgical inculturation in Indonesia. As an institution historically rooted in Western traditions, the Catholic Church is required to engage in dialogue with the cultural diversity of the Indonesian archipelago, which is marked by complex symbols, values, and religious expressions. Liturgical inculturation represents an encounter between faith and culture that seeks to preserve the theological meaning of the liturgy while fostering the development of local religious identity. Within this context, the study aims to explore the forms, meanings, and social implications of inculturation practices in the Indonesian Catholic Church. The primary objective is to analyze the processes and meanings of inculturation in the implementation of Catholic liturgy, particularly in the adaptation of symbols, language, and local cultural expressions within the Eucharistic celebration. This research employs a descriptive qualitative method with a phenomenological approach, informed by the social construction theory of Peter L. Berger and Thomas Luckmann. The findings reveal that liturgical inculturation in Indonesia is not merely aesthetic or symbolic, but constitutes a dialogical and reflective process that integrates Gospel values with local cultural traditions. Furthermore, inculturation strengthens the congregation’s sense of belonging while broadening the understanding of catholicity as a universal communion that embraces cultural diversity.